Gravity model as the tool for internal migration analysis in Poland in 2004-2010 - Michal Bernard Pietrzak; Justyna Wilk; Stanislaw Matusik (Institute of Economic Research (IER), 2013)
Population migration is a long-lasting process affected by many factors. The analysis of its effects is a typical research approach to its interpretation. The object of the paper is to investigate migration phenomenon by means of gravity model application. It helps to explain variations in the level of migration flows between and within regions, to determine its effects and reasons including geographical factor. The analysis covers internal migration in Poland in the period of 2004-2010. Inter- and intraregional flows at NTS-2 level were considered. Two periods of time regarding economic situation in Poland were specified: 2004-2007, 2008-2010. Key economic factors (GDP, capital expenditures, unemployment, wages and salaries) were used as explanatory variables. Distances between regions were determined on their centroids. The research results confirmed that regional economic indicators are the determinants of internal migration directions in Poland whilst overall economic situation affects its intensity. The regions featuring relatively good economic situation are the centres of population inflow (particularly from neighbouring locations) whereas the other perform the role of 'demographic resources' for better developed voivodships.
Keywords: J11; O11; R11; R23; 330; gravity model; internal migration; economic determinants of migration